Myeloid cell expression of CD200R is modulated in active TB disease and regulates Mycobacterium tuberculosis infection in a biomimetic model - Ahmed, Mohamed; Tezera, Liku B.; Herbert, Nicholas; Chambers, Mark; Reichmann, Michaela T.; Nargan, Kievershen; Kloverpris, Henrik; Karim, Farina; Hlatshwayo, Mbali; Madensein, Rajhmun; Habesh, Munir; Hoque, Monjural; et al. (Frontiers in Immunology, 2024)
A robust immune response is required for resistance to pulmonary tuberculosis (TB), the primary disease caused by Mycobacterium tuberculosis (Mtb). However, pharmaceutical inhibition of T cell immune checkpoint molecules can result in the rapid development of active disease in latently infected individuals, indicating the importance of T cell immune regulation.In this study, we investigated the potential role of CD200R during Mtb infection, a key immune checkpoint for myeloid cells. Expression of CD200R was consistently downregulated on CD14 + monocytes in the blood of subjects with active TB compared to healthy controls, suggesting potential modulation of this important anti-inflammatory pathway. In homogenized TB-diseased lung tissue, CD200R expression was highly variable on monocytes and CD11b + HLA-DR + macrophages but tended to be lowest in the most diseased lung tissue sections. This observation was confirmed by fluorescent microscopy, which showed the expression of CD200R on CD68 + macrophages surrounding TB lung granuloma and found expression levels tended to be lower in macrophages closest to the granuloma core and inversely correlated with lesion size. Antibody blockade of CD200R in a biomimetic 3D granuloma-like tissue culture system led to significantly increased Mtb growth. In addition, Mtb infection in this system reduced gene expression of CD200R. These findings indicate that regulation of myeloid cells via CD200R is likely to play an important part in the immune response to TB and may represent a potential target for novel therapeutic intervention.